PROSES KREATIF KIRUN DALAM KESENIAN KETOPRAK DAN LUDRUK - BANGKIT ALFARIZS, RIZCKY; ABDILLAH, AUTAR (APRON Jurnal Pemikiran Seni Pertunjukan, 2020)
ABSTRACT Kirun is a talented ludruk artist and also a talented ketoprak. When he was young he often studied and played ludruk in various places. People can learn to be funny but there are people who are really funny. Abah Kirun made this hermitage intending to treat traditional arts and culture. In addition, Abah Kirun preserves art so it is not lost by the current of globalization. He was also born from ludruk and ketoprak artists since he was young. With the creative ideas from Abah Kirun, Indonesian people love their culture more. In the art of Ketoprak and Ludruk Abah Kirun has a unique creativity starting from the cultivation of the play to another interesting thing there are several performances of Ludruk from Abah Kirun, Jula Juli. Her chants are in round 4 or mid-staging. Abah Kirun also often directs Ketoprak and Ludruk which he created himself. The research method used is qualitative. Data collection techniques used in this study were interviews, observation, and documentation validated using triangulation of sources, techniques, and methods. Furthermore, the data obtained will be reduced data, data interventions, and drawing conclusions The results of this study indicate that Ketoprak and Ludruk Abah Kirun work together with one another. Starting from the method of cultivation of the round, cultivation techniques, factors of creativity to those raised in cultivation are almost synergized with each other. The commercial problems of Ketoprak and Ludruks art have an impact on the continuity of this traditional art, so there are also several factors in creativity ranging from environmental factors to social factors. Frequent achievement also increases the selling price and manages the creativity of Ketoprak and Ludruk Abah Kirun Abah Kirun. Keywords: Creativity, Ludruk, Ketoprak, Abah Kirun